2010
DOI: 10.2471/blt.08.057471
|View full text |Cite
|
Sign up to set email alerts
|

Expiry of medicines in supply outlets in Uganda

Abstract: a Problem The expiry of medicines in the supply chain is a serious threat to the already constrained access to medicines in developing countries. Approach We investigated the extent of, and the main contributing factors to, expiry of medicines in medicine supply outlets in Kampala and Entebbe, Uganda. A cross-sectional survey of six public and 32 private medicine outlets was done using semi-structured questionnaires. Local setting The study area has 19 public medicine outlets (three non-profit wholesalers, 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 1 publication
3
65
2
3
Order By: Relevance
“…Our study findings confirm the results of an early systematic review by Jones et al [39], which demonstrated PHC health workers’ concerns about the reliability and cost of POC diagnostics. In line with the study findings, supply chain management systems of essential health commodities have been reported as experiencing problems leading to stock out and expiry of essential reagents [40]. The importance of maintaining enhanced, interactive and highly responsive supply chain management for maintaining adequate quantities of testing stocks is essential [41].…”
Section: Discussionmentioning
confidence: 64%
“…Our study findings confirm the results of an early systematic review by Jones et al [39], which demonstrated PHC health workers’ concerns about the reliability and cost of POC diagnostics. In line with the study findings, supply chain management systems of essential health commodities have been reported as experiencing problems leading to stock out and expiry of essential reagents [40]. The importance of maintaining enhanced, interactive and highly responsive supply chain management for maintaining adequate quantities of testing stocks is essential [41].…”
Section: Discussionmentioning
confidence: 64%
“…Drug expiry was a problem in some areas but not others. In Uganda, nearly half of the shops reported cases of drugs expiring, whereas only one case was observed in Somaliland [17,29]. Generic substitution was rarely done; in South Africa for instance, only 14% of pharmacists substituted branded drugs, despite the fact that nearly half of prescribed medicines had generic equivalents [41].…”
Section: Resultsmentioning
confidence: 99%
“…We assumed that drugs would be purchased or provided for all people eligible for MDA and that any unused drugs are wasted: i.e. they are not used in later MDA rounds, because they were either distributed and not consumed or they were lost, damaged, or expired [9], [26], [29].…”
Section: Methodsmentioning
confidence: 99%